2016
DOI: 10.1002/jcla.21917
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Serum and Salivary Cytokines Level With Clinical Parameters in Metabolic Syndrome With Periodontitis

Abstract: Proinflammatory marker TNF-α has correlation with clinical parameters in patients of MS having PD. The study suggests level of salivary TNF-α may be utilized as a surrogate marker of MS and PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 30 publications
1
11
0
1
Order By: Relevance
“…However, our results showed that there were no correlation of salivary TNF‐α concentrations with other clinical parameters of gCP patients in both melatonin and placebo subjects. This comes in accordance with other studies; however, Chauhan et al results indicated the opposite in chronic periodontitis patients suffering from metabolic syndrome.…”
Section: Discussionsupporting
confidence: 92%
“…However, our results showed that there were no correlation of salivary TNF‐α concentrations with other clinical parameters of gCP patients in both melatonin and placebo subjects. This comes in accordance with other studies; however, Chauhan et al results indicated the opposite in chronic periodontitis patients suffering from metabolic syndrome.…”
Section: Discussionsupporting
confidence: 92%
“…Saliva is now regarded as a pool of biological markers and therefore has great potential for use in the prediction and diagnosis of systemic and localized diseases [ 30 ]. Many researchers have attempted to find useful biomarkers such as TNF- α , IL-10, IL-17, IL-12, and IL-1 β [ 10 , 31 33 ] in saliva that are associated with periodontitis to help predict or diagnose T2DM. However, low expression biomarkers are easily affected by systemic health status, which prevents these immunological markers from being widely employed [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…(47) We also decided to estimate the afore-mentioned cytokines in unstimulated saliva because collection of saliva is a non invasive method and easily harvested in large amount and reflects all soluble mediators and cytokines in the periodontal tissues as most of the gingival sulcular fluid seeps into saliva. (48) To the best of our knowledge, there is no studies available until now investigating the salivary RANKL levels in chronic periodontitis patients who are maintained on a daily stable dose of statins. However, El-Sharkawy et al, 2010, assessed salivary RANKL in periodontitis patients after supplementation with omega-3 fatty acids combined with low dose of aspirin and demonstrated greater reduction in salivary RANKL when compared to the non-omega-3 E.D.J.…”
Section: Discussionmentioning
confidence: 99%